Opportunities and challenges of new classification systems for personality disorders: commentary on “Clinical utility of the AMPD: a 10th year anniversary review” - Herpertz, Sabine; Bertsch, Katja (Personality disorders, 2022)
At the time of publication of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition alternative model of personality disorders, skepticism regarding the clinical utility of a dimensional conceptualization of personality disorders was high including questions about its feasibility for clinicians, its reliability, predictive value, and implications for science and treatment. Following huge research activities summarized by the article of Bach and Tracy (2022), there is meanwhile convincing evidence that a dimensional classification of personality disorders that meets with high utility for clinical decision-making is accepted by clinicians and meets with patients´ needs because it can be easily connected with treatment planning oriented at functional impairments rather than diagnostic categories. Being close to mechanistic models of psychopathology, the alternative model of personality disorders provides a suitable framework to converge self- and interpersonal dysfunctioning indicated in Criterion A with (sub-)domains of the Research Domain Criteria and Hierarchical Taxonomy of Psychopathology systems and, thus, to inspire research to better understand the psychological and neurobiological mechanisms of change. (PsycInfo Database Record (c) 2022 APA, all rights reserved)